Pengaruh Penerapan Media Pembelajaran Mind Map Terhadap Daya Ingat Siswa Pada Materi Ski Kelas VIII di MTSN 3 Pasaman - Diana Shaleh Putri; Darul Ilmi; Jasmienti Jasmienti; Alimir Alimir (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Abstract. The background of this research is the students' low memory for class VIII SKI material at MTsN 3 Pasaman, which the researchers can see from the low UTS scores and the way students learn during the SKI learning process. In learning the teacher still uses the lecture method so that students tend to feel bored and not focus on following the learning process. One effort that is thought to be able to overcome this is by applying mind maps to the SKI subject for class VIII students at MTsN 3 Pasaman. The purpose of this study was to find out whether there was an effect of applying mind maps to students' memory in class VIII SKI material at MTsN 3 Pasaman. This research is a quasi-experimental quantitative research with a true experimental research design. The population in this study were all students of class VIII at MTsN 3 Pasaman. Sampling was done randomly or Random Sampling. The sample in this study amounted to 68 students. Students of class VIII 3 as the experimental class and students of class VIII 6 as the control class. The instrument used by the researcher was the results of the students' SKI posttest in the form of multiple choice of 25 questions with the material on the Intellectual Glory of Muslim and Ulama Sciences during the Abbasid Daulah period. The results showed that the proportion of mastery of the experimental class students was higher than the proportion of mastery of the control class students. In the experimental class, the number of students who completed there were 27 people with a proportion of 79% and those who did not complete were 7 people with a proportion of 21% of the number of students in the experimental class, namely 34 students. Whereas in the control class, 1 person completed with a proportion of 3% and students did not complete 33 students with a proportion of 97% of 34 students. so that there is a 35.5% effect of applying the mind map on students' memory in grade VIII SKI material at MTsN 3 Pasaman. From the results of the hypothesis test tcount = 8.762 and ttable 1.6909. Because tcount > ttable means that H0 is rejected at the significant level α = 0.05. From these results it can be written reject H0 and accept H1, meaning that there is an influence of the application of the mind map media on students' memory on the intellectual triumph of Muslim scientists and scholars during the Abbasid dynasty in class VIII MTsN 3 Pasaman.